Albumin excretion rate among patients with diabetic retinopathy - Makbul Aman (Caspian Journal of Internal Medicine, 2020)
Background: Chronic microvascular complications consist of diabetic nephropathy (DN), diabetic retinopathy (DR), and diabetic neuropathy. Diabetic nephropathy is assessed through albuminuria, and diabetic retinopathy is assessed through fundoscopy. Several studies have assessed the albuminuria in diabetic retinopathy but have found inconclusive results. This study aims to investigate the albumin excretion rate in patients with diabetic retinopathy. Methods: A cross sectional design was applied in this study. The diagnosis of type 2 diabetes mellitus was determined based on the anamnesis and laboratory examinations. The study was conducted at Dr. Wahidin Sudirohusodo Hospital and Hasanuddin University Hospital in Makassar during November 2018 until April 2019. The stages of diabetic retinopathy were based on funduscopic examinations. In addition, the blood pressure, BMI, albumin excretion rate, lipid profile, and HbA1C were also examined. Chi Square and Kappa tests were performed in the statistical analysis. Results: 120 subjects with type 2 diabetes mellitus were observed. Of the total subjects, the number of females within the age of 36-79 years made up the biggest fraction. There was a significant relation between hypertension comorbidity with the albumin excretion rate and grading diabetic retinopathy where the A3 and proliferative diabetic retinopathy (PDR) percentages were higher in the hypertension group at 68.8% and 54.5%. There was also a significant correlation between incidence of albuminuria with diabetic retinopathy.  Particularly, proliferative diabetic retinopathy (PDR) remained associated with albuminuria, while non-proliferative diabetic retinopathy (NPDR) was related to non-albuminuria. Conclusion: Albuminuria incidence confirms association with diabetic retinopathy grading.